Rocksalt-structured MgZnO-based UV-C lamp emitting in 190–220 nm spectral range using 146 nm line of Kr2* generated by dielectric barrier discharge - Kotaro Ogawa; Toshiki Mitomi; Hideki Yajima; Wataru Kosaka; Hiroya Kusaka; Go Kobayashi; Tomohiro Yamaguchi; Tohru Honda; Kentaro Kaneko; Shizuo Fujita; Izumi Serizawa; Takeyoshi Onuma (Applied Physics Express)
Rocksalt (RS)-structured Mg _0.97 Zn _0.03 O polycrystalline film, which was grown on a quartz glass substrate with the hot-wall-type mist chemical vapor deposition method, exhibited a vacuum ultraviolet photoluminescence at 6.39 eV (194 nm) at 300 K. The film was then used as the emission layer of a spot-irradiation lamp that had the 146 nm line of a Kr _2 ^∗ excimer lamp as an excitation source. The UV-C lamp exhibited a distinct peak at 6.14 eV (202 nm) spreading over a range of 190–220 nm. The result is the first demonstration of a RS-MgZnO-based UV-C lamp.